The commodification of English language in Chinese tourism: a case study of the Palace Museum - Xiao, Rong; Pang, Chaowei (Penerbit Universiti Kebangsaan Malaysia, 2024)
Based on an empirical case study in the Palace Museum in Beijing, China, this article sketches out the functional usefulness of the English language from an economic perspective, providing an empirical estimation of the economic values of English in the linguistic landscape of the Chinese tourism marketplace. It develops a topical understanding of the commodification of the English language by taking into consideration both the English language as a commodity and the process of English language commodification. Research data were gathered from a number of sources, including English introductory signboards on-site, questionnaire surveys, and interviews. Analysis shows that three major dimensions of economic value could be detected from the use of English in the Palace Museum: the communicative value, the informative value, and the symbolic value. While this study contributes a socioeconomic perspective to the English language in the Chinese tourism context, it could shed light on the adoption and economic values of the English language in similar contexts in the world.